2016
DOI: 10.7603/s40602-016-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community-Based Cardiac Rehabilitation on Clinical Parameters of Patients with Cardiovascular Diseases

Abstract: Background:Cardiac rehabilitation (CR) programmes have been shown to improve patient outcomes, but vary widely in their components. The impact of Singapore’s CR programme on clinical outcomes is currently not known.Objective:To evaluate the effects of a community-based CR programme on important clinical parameters in patients with cardiovascular disease in Singapore.Method:A retrospective cohort study was conducted. Cardiovascular patients who had completed a hospital-based CR programme were included. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Compared to those patients who received usual care, these patients were found to have an overall improvement of 12% in "bad" cholesterol, 7.8% triglycerides, 7% total cholesterol, 8.2% fasting blood glucose, 2.5% systolic BP and 3.5% diastolic BP after one year of community rehabilitation [2].…”
Section: Tay Hung Yongmentioning
confidence: 96%
“…Compared to those patients who received usual care, these patients were found to have an overall improvement of 12% in "bad" cholesterol, 7.8% triglycerides, 7% total cholesterol, 8.2% fasting blood glucose, 2.5% systolic BP and 3.5% diastolic BP after one year of community rehabilitation [2].…”
Section: Tay Hung Yongmentioning
confidence: 96%
“…Community-based rehabilitation programmes may help improve the accessibility of and compliance with cardiac rehabilitation in HF patients in the Asia-Pacific region and are associated with favourable CV health benefits, including improved CV markers. 59,60 CIED therapy for HF includes the implantable cardioverter defibrillator and cardiac resynchronisation therapy. Randomised trials have demonstrated that the use of CIEDs in carefully selected patients reduces the risk of death across a relatively wide range of clinical scenarios.…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Uptake to maintenance CBCR programmes is hindered by the inadequate availability of such services [23,24] with the majority of these programmes delivered by HCPs such as physiotherapists [25,26], GPs [27] or a multidisciplinary team including cardiologists, physiotherapist, CR nurses and exercise physiologists [16,28]. Traditionally long-term exercise programmes have been delivered for individual CDs such as CR and pulmonary rehabilitation.…”
Section: Introductionmentioning
confidence: 99%